2021
DOI: 10.1186/s40709-021-00134-9
|View full text |Cite
|
Sign up to set email alerts
|

Different solutions lead to similar life history traits across the great divides of the amniote tree of life

Abstract: Amniote vertebrates share a suite of extra-embryonic membranes that distinguish them from anamniotes. Other than that, however, their reproductive characteristics could not be more different. They differ in basic ectothermic vs endothermic physiology, in that two clades evolved powered flight, and one clade evolved a protective shell. In terms of reproductive strategies, some produce eggs and others give birth to live young, at various degrees of development. Crucially, endotherms provide lengthy parental care… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 174 publications
(253 reference statements)
1
14
0
Order By: Relevance
“…Body size is known to evolve under different selective pressures from life history (e.g. temperature; Tinkle et al 1970), but through allometric constraints selection pressures on body size can indirectly influence traits that are related to the fast/slow life history spectrum (Bauwens and Díaz‐Uriarte 1997, Bakewell et al 2020, Meiri et al 2021). We therefore placed species on a body size‐independent fast/slow life history continuum using phylogenetic factor analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Body size is known to evolve under different selective pressures from life history (e.g. temperature; Tinkle et al 1970), but through allometric constraints selection pressures on body size can indirectly influence traits that are related to the fast/slow life history spectrum (Bauwens and Díaz‐Uriarte 1997, Bakewell et al 2020, Meiri et al 2021). We therefore placed species on a body size‐independent fast/slow life history continuum using phylogenetic factor analysis.…”
Section: Introductionmentioning
confidence: 99%
“…They are the major groups of freshwater, land, air, and marine life, and they are the only two major groups that have adapted to dry environments. The other major group is the amniotes, whose live members are reptiles, birds, and warm-blooded animals [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using the data in TetraDENSITY (Santini et al 2018), across 11,085 populations with reported sampling area, I obtained a log-log relationship with sampling area explaining 68% of the variation in density. Across 19,494 amniote populations a model with log-mass (from Meiri et al, 2021, slope = -0.56, not -0.75) explained only 43% of the variation in log-density.…”
mentioning
confidence: 96%